2022
DOI: 10.1016/j.cgh.2021.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Financial Burden of Digestive Diseases in a Commercially Insured Population

Abstract: BACKGROUND & AIMS:Digestive diseases represent a diverse group of clinical conditions that impact the population.Their heterogeneity in classification, presentation, acuity, chronicity, and need for drug therapy presents a challenge when comparing and contrasting the burden associated with these conditions. Prior studies use an outdated classification system and aggregate costs at the population level or focus on specific diseases, limiting the ability to characterize the overall landscape. Our aim was to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(31 reference statements)
1
18
1
3
Order By: Relevance
“…In the general population, the incidence rate of AP ranges from 10 to 44 per 100,000/year, 6 being one of the leading causes of hospital admission and expenses for digestive diseases 7 . Patients with IBD seem to be at increased risk for acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…In the general population, the incidence rate of AP ranges from 10 to 44 per 100,000/year, 6 being one of the leading causes of hospital admission and expenses for digestive diseases 7 . Patients with IBD seem to be at increased risk for acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…Digestive system diseases, including fatty liver diseases (FLDs), liver and intestinal ischemia-reperfusion injury (IRI), hepatitis B virus (HBV), pancreas diseases, and inflammatory bowel diseases (IBDs), are the most common clinical diseases. 653 , 654 Increasing evidence has suggested that changes in SIRT activity and expression are associated with etiology of various digestive diseases. 280 , 655 As discussed below, SIRTs play an important role in maintaining the homeostasis of digestive system function and participating in the occurrence and development of digestive diseases (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent acute pancreatitis (RAP) is a common clinical problem, among the first causes of emergency and expense for gastroenterological pathologies in US [11,12]. Common complications such as the evolution to episodes of acute pancreatitis, the onset of diabetes or the progression to chronic pancreatitis represent an eventuality with a serious impact on the patient's quality of life and on healthcare costs [13]. About one-third of cases of acute pancreatitis have a recurrence, resulting in the onset of chronic pancreatitis over time [14].…”
Section: Recurrent Acute Pancreatitismentioning
confidence: 99%